Vital for Democracy, but Do They Realise It? Europe's Youth and the 2014 Elections. Issue 1 (June 2013) - Prainsack, Ines Elise; Vodanović, Andrea
In this article, we first highlight the recent trends of voter turnout for European elections and analyse whether or not young people care about these elections. Then we discuss the role and potential influence of social media on elections and their results. Finally, we outline why an investment in youth will 'pay off', as one could compare it with the relationship between a bank and its customers (even though banks are not the most popular objects nowadays, but then neither are politicians). If I open an account at a bank when I am young, I get good offers and good service; the bank looks after my interest, and it is likely that I will stay at this bank for the rest of my life. The same could be true for political parties: they invest in young people, who might become the voters and leaders of the party in the future.